Magnesian castable with low-grade magnesite tailings as aggregate

By using low-grade magnesite tailings as aggregate, combined with admixtures, and bonding agents, magnesium castables are made, which solves the resource waste and environmental pollution problems of low-grade magnesite tailings after ore dressing, and achieves the high-temperature strength and environmental protection performance of magnesite castables.

CN119707511APending Publication Date: 2025-03-28HAICHENG CITY ZHONGXING MAGNESIA SYNTHETIC MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411868645.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize low-grade magnesite tailings after ore dressing, resulting in waste of resources and environmental pollution.

Method used

Low-grade magnesite tailings are used as aggregate, combined with admixtures, admixtures and bonding agents to make magnesium castable. The composition of the castable includes 55 to 65 wt% low grade magnesite tailings aggregate, 20 to 30 wt% admixture, 5 to 8 wt% admixture, and 7 to 10 wt% binding agent.

Benefits of technology

The magnesium castable material produced has good high temperature strength, thermal vibration resistance and slag resistance, which solves the utilization problem of low-grade magnesite tailings, saves mineral resources, protects the environment, and is energy-saving and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005195172530000071
    Figure BDA0005195172530000071
Patent Text Reader

Abstract

The invention relates to a magnesium castable taking low-grade magnesite tailings as aggregate, which is prepared from the following components in percentage by weight: 55-65 percent of low-grade magnesite tailings aggregate with the particle size of 0.25-20 mm, 45-50 percent of admixture, 50-55 percent of admixture and 5-10 percent of binding agent, the low-grade magnesite tailings aggregate with the particle size of 0.25-20 mm accounts for 45-50 percent of the low-grade magnesite tailings aggregate with the particle size of 0.25-20 mm, and the admixture accounts for 50-55 percent of the low-grade magnesite tailings aggregate with the particle size of less than 5.0 mm and greater than or equal to 0.25 mm. 20 to 30 wt% of an admixture; 5-8 wt% of an additive; and 7-10 wt% of a binding agent. The low-grade magnesite tailing castable has the beneficial effects that the castable product prepared by taking the low-grade magnesite tailing which cannot be used for preparing a magnesium material as a main material has good high-temperature strength, thermal shock resistance and slag resistance, the problems of utilization and discharge of the low-grade magnesite tailing after mineral separation are solved, mineral resources are saved, the surrounding environment is protected, and the low-grade magnesite tailing castable is suitable for industrial production. And energy saving and environmental protection are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mineral product processing and environmental protection, in particular to a magnesium castable using low-grade magnesite tailings as aggregate. Background Art

[0002] Castables are a commonly used construction material, widely used in metallurgy, coal coking, petrochemical, furnaces and other fields, as well as in construction, roads, bridges, tunnels and other projects. Refractory castables are a mixture of refractory aggregates, powders and binders. After adding water or other liquids, they are suitable for construction by pouring and vibration methods. They can also be prefabricated into prefabricated parts with specified shapes and sizes for the construction of linings of industrial furnaces such as blast furnaces and coke ovens. In recent years, affected by the international environment, especially with the downward pressure on the economy of the entire steel industry, the market competition pressure in the refractory industry has become increasingly greater, the profit margin of products has gradually shrunk, and the survival space of refractory manufacturers has also been seriously challenged. At the same time, with the vigorous development of the steel industry, the consumption of mineral resources has increased, and resources have become increasingly scarce. In addition, my country has abundant reserves of magnesite resources. The proven reserves are about 3.1 billion tons, accounting for a quarter of the world's total reserves. They are mainly distributed in Liaoning Province and Shandong Province, accounting for about 95% of the country's total reserves, of which low-grade magnesite reserves are as high as 540 million tons. The large amount of waste of magnesite tailings after existing beneficiation not only occupies a large amount of land resources, causing a huge waste of resources, but also leads to ecological damage and serious environmental pollution. Therefore, the development and utilization of low-grade magnesite is imminent. Summary of the invention

[0003] In order to overcome the defects of the prior art, the technical problem solved by the present invention is to provide a magnesia castable with low-grade magnesite tailings as aggregate, and the low-grade magnesite tailings that cannot be used to prepare magnesia materials are used as the main material. The prepared castable product has good high-temperature strength, thermal vibration resistance and slag resistance, solves the utilization and discharge problems of low-grade magnesite tailings after mineral processing, saves mineral resources, protects the surrounding environment, and is energy-saving and environmentally friendly.

[0004] In order to achieve the above object, the present invention adopts the following technical solutions:

[0005] A magnesium castable with low-grade magnesite tailings as aggregate, characterized in that the castable is made of low-grade magnesite tailings aggregate with a particle size of 0.25 to 20 mm, admixture, additive and binder, and the proportion of each component by weight is:

[0006] Low-grade magnesite tailings aggregate with a particle size of 0.25-20mm: 55-65wt%, of which 0.25mm≤particle size<5.0mm accounts for 45-50wt%, 5.0mm≤particle size<20mm accounts for 50-55wt%;

[0007] Admixture: 20-30wt%;

[0008] Admixture: 5-8wt%;

[0009] Binder: 7-10wt%;

[0010] The admixture is low-grade magnesite tailings, 1-3wt% magnesium chloride powder is added, and the fine powder of calcined and ground clinker particles is obtained, wherein particles with a particle size of 0.088 mm or less and a particle size of 0.25 mm or less account for 20-30wt%, and particles with a particle size of 0.088 mm or less account for 70-80wt%.

[0011] The admixture comprises the following raw materials in weight percentage: 2-4wt% SiO2 ultrafine powder, 2-4wt% Al2O3 powder, 0.1-0.8wt% hydroxypropyl methylcellulose (HPMC), 0.1-0.15% sodium tripolyphosphate, and 0.05-0.1% sodium hexametaphosphate;

[0012] The binder is a mixture of water glass, ethyl silicate and polyaluminium chloride, wherein the weight percentages of water glass, ethyl silicate and polyaluminium chloride are 4-6:0.3-0.7:0.03-0.07.

[0013] Furthermore, the SiO2 content in the SiO2 ultrafine powder is greater than 98wt% and the particle size is less than 1μm;

[0014] Furthermore, the particle size of the Al2O3 powder is less than 0.088 mm.

[0015] Furthermore, a method for preparing a magnesia castable using low-grade magnesite tailings as aggregate is characterized by comprising the following steps:

[0016] Step 1: crush and screen the selected low-grade magnesite tailings, and select the particles with a particle size of 0.25 to 20 mm as the low-grade magnesite tailings coarse material, i.e., aggregate, wherein the particles with a particle size of 0.25 mm ≤ < 5.0 mm and the particles with a particle size of 5.0 mm ≤ < 20 mm are classified and placed;

[0017] Step 2, adding 1-3wt% of magnesium chloride powder to the remaining materials screened in step 1, calcining at 900-1000° C. for 1-3 hours, and then crushing, grinding and screening to obtain fine powder with a particle size of less than 0.088 mm and granular material with a particle size of 0.088-0.25 mm, i.e., admixture;

[0018] Step 3, weighing 20-30 wt% of admixture and 5-8 wt% of admixture according to weight percentage, putting them into a vibration mill and grinding them for 10 minutes to obtain a mixture;

[0019] Step 4: weigh 55-65wt% of the aggregate prepared in step 1 and 7-10wt% of the binder by weight percentage, add them together with the mixture prepared in step 3 into a mixer, and stir for 3-5 minutes to obtain a castable.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1) The castable of the present invention uses low-grade magnesite tailings that cannot be used to prepare magnesia materials as the main material, which solves the problem of discharge and reuse of low-grade magnesite tailings after ore dressing, saves mineral resources, protects the surrounding environment, and is energy-saving and environmentally friendly;

[0022] 2) The castable of the present invention, the admixture is low-grade magnesite tailings and a certain amount of magnesium chloride is added and calcined, which can effectively increase the volume density of the castable prepared later and effectively improve the fluidity of the castable prepared later;

[0023] 3) The castable of the present invention has SiO2 ultrafine powder and Al2O3 powder added to the raw materials, which can fill the pores and increase the density and strength of the material. In addition, when SiO2 ultrafine powder and Al2O3 powder coexist, mullite phase is more easily generated, thereby enhancing the high temperature strength, thermal vibration resistance and slag resistance of the castable. DETAILED DESCRIPTION

[0024] The technical solution of the present invention will be further clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] The low-grade magnesite tailings used in the embodiment of the present invention are magnesite tailings after being selected by a certain ore dressing plant in Haicheng, Liaoning Province, and its chemical composition is MgO 35-41%, CaO 8.66-15.21%, SiO2 2.11-6.22%, Al2O3 0.52-1.28%, Fe2O3 2.32-3.82% by weight, and the remainder is trace impurities.

[0026] A magnesium castable with low-grade magnesite tailings as aggregate, which is made of low-grade magnesite tailings aggregate with a particle size of 0.25 to 20 mm, admixtures, additives and binders, and the proportions of each component by weight are as follows:

[0027] Low-grade magnesite tailings aggregate with a particle size of 0.25-20mm: 55-65wt%, of which 0.25mm≤particle size<5.0mm accounts for 45-50wt%, 5.0mm≤particle size<20mm accounts for 50-55wt%;

[0028] Admixture: 20-30wt%;

[0029] Admixture: 5-8wt%;

[0030] Binder: 7-10wt%;

[0031] The admixture is low-grade magnesite tailings, 1-3wt% magnesium chloride powder is added, and the fine powder of calcined and ground clinker particles is obtained, wherein particles with a particle size of 0.088 mm or less and a particle size of 0.25 mm or less account for 20-30wt%, and particles with a particle size of 0.088 mm or less account for 70-80wt%.

[0032] The admixture comprises the following raw materials in weight percentage: 2-4wt% SiO2 ultrafine powder, 2-4wt% Al2O3 powder, 0.1-0.8wt% hydroxypropyl methylcellulose (HPMC), 0.1-0.15% sodium tripolyphosphate, and 0.05-0.1% sodium hexametaphosphate;

[0033] The binder is a mixture of water glass, ethyl silicate and polyaluminium chloride, wherein the weight percentages of water glass, ethyl silicate and polyaluminium chloride are 4-6:0.3-0.7:0.03-0.07.

[0034] Furthermore, the SiO2 content in the SiO2 ultrafine powder is greater than 98wt% and the particle size is less than 1μm;

[0035] Furthermore, the particle size of the Al2O3 powder is less than 0.088 mm.

[0036] Furthermore, a method for preparing a magnesium castable using low-grade magnesite tailings as aggregate comprises the following steps:

[0037] Step 1: crush and screen the selected low-grade magnesite tailings, and select the particles with a particle size of 0.25 to 20 mm as the low-grade magnesite tailings coarse material, i.e., aggregate, wherein the particles with a particle size of 0.25 mm ≤ < 5.0 mm and the particles with a particle size of 5.0 mm ≤ < 20 mm are classified and placed;

[0038] Step 2, adding 1-3wt% of magnesium chloride powder to the remaining materials screened in step 1, calcining at 900-1000° C. for 1-3 hours, and then crushing, grinding and screening to obtain fine powder with a particle size of less than 0.088 mm and granular material with a particle size of 0.088-0.25 mm, i.e., admixture;

[0039] Step 3, weighing 20-30 wt% of admixture and 5-8 wt% of admixture according to weight percentage, putting them into a vibration mill and grinding them for 10 minutes to obtain a mixture;

[0040] Step 4: Weigh 50-60wt% of the aggregate prepared in step 1 and 5-12wt% of the binder according to weight percentage, add them together with the mixture prepared in step 3 into a mixer, and stir for 3-5 minutes to obtain a castable.

[0041] [Example 1]:

[0042] A magnesium castable with low-grade magnesite tailings as aggregate, which is made of low-grade magnesite tailings aggregate with a particle size of 0.25 to 20 mm, admixtures, additives and binders, and the proportions of each component by weight are as follows:

[0043] Low-grade magnesite tailings aggregate with a particle size of 0.25-20 mm: 60wt%, of which 0.25mm≤particle size<5.0mm accounts for 47.5wt%, and 5.0mm≤particle size<20mm accounts for 52.5wt%;

[0044] Admixture: 25wt%;

[0045] Admixture: 6.5wt%;

[0046] Binder: 8.5wt%;

[0047] The admixture is low-grade magnesite tailings, 2wt% magnesium chloride powder is added, and the fine powder of calcined and ground clinker particles is obtained, wherein particles with a particle size of 0.088 mm or less and a particle size of 0.25 mm or less account for 25wt%, and particles with a particle size of 0.088 mm or less account for 75wt%;

[0048] The admixture comprises the following raw materials in weight percentage: 2.9wt% SiO2 ultrafine powder, 2.9wt% Al2O3 powder, 0.5wt% hydroxypropyl methylcellulose (HPMC), 0.125% sodium tripolyphosphate, and 0.075% sodium hexametaphosphate;

[0049] The binder is a mixture of water glass, ethyl silicate and polyaluminium chloride, wherein the weight percentage of water glass, ethyl silicate and polyaluminium chloride is 5:0.5:0.05.

[0050] Furthermore, the SiO2 content in the SiO2 ultrafine powder is greater than 98wt% and the particle size is less than 1μm;

[0051] Furthermore, the particle size of the Al2O3 powder is less than 0.088 mm.

[0052] Furthermore, a method for preparing a magnesium castable using low-grade magnesite tailings as aggregate comprises the following steps:

[0053] Step 1: crush and screen the selected low-grade magnesite tailings, and select the particles with a particle size of 0.25 to 20 mm as the low-grade magnesite tailings coarse material, i.e., aggregate, wherein the particles with a particle size of 0.25 mm ≤ < 5.0 mm and the particles with a particle size of 5.0 mm ≤ < 20 mm are placed in a classified manner for the convenience of weighing and batching later;

[0054] Step 2: Add 2 wt% of magnesium chloride powder to the remaining materials screened in step 1, i.e., low-grade magnesite tailings with a particle size of less than 0.25 mm and a particle size of ≥20 mm, calcine at 950° C. for 2 h, and then crush, grind and screen to obtain fine powder with a particle size of less than 0.088 mm and granular material with a particle size of 0.088 to 0.25 mm, i.e., admixture;

[0055] Step 3, weighing 25wt% of the admixture and 6.5wt% of the admixture according to weight percentage, putting them into a vibration mill and grinding them for 10 minutes to obtain a mixture;

[0056] Step 4: Weigh 60wt% of the aggregate prepared in step 1 by weight percentage, of which 47.5wt% are particles with a diameter of 0.25mm≤<5.0mm, 52.5wt% are particles with a diameter of 5.0mm≤<20mm, and 8.5wt% are binders. Add them together with the mixture prepared in step 3 into a mixer and stir for 5 minutes to obtain a castable.

[0057] In this embodiment, step two, high-temperature calcination of the admixture can burn off moisture and harmful impurities in the low-grade magnesite tailings, increase the MgO content therein, and at the same time add an appropriate amount of magnesium chloride, which can effectively improve the density of the castable structure, reduce the porosity, and optimize the various performance indicators of the castable until they reach the optimal level.

[0058] In this embodiment, in step three, the admixture is ground together with the admixture, which can reduce the amount of water added to the castable when used.

[0059] Improve the fluidity of the castable and significantly improve the qualification rate and quality of the cast products of prefabricated products.

[0060] In this embodiment, SiO2 ultrafine powder and Al2O3 powder are added to the castable raw material, which can effectively fill the pores and increase the density and strength of the material. In addition, when SiO2 ultrafine powder and Al2O3 powder coexist, mullite phase is more easily generated, thereby enhancing its high temperature strength, thermal vibration resistance and slag resistance.

[0061] Furthermore, when pouring is carried out on site, 5 to 10 wt % of water is added to the semi-dry castable prepared in step 4 as needed, and the mixture is stirred evenly before construction.

[0062] [Example 2]:

[0063] A magnesium castable with low-grade magnesite tailings as aggregate, which is made of low-grade magnesite tailings aggregate with a particle size of 0.25 to 20 mm, admixtures, additives and binders, and the proportions of each component by weight are as follows:

[0064] Low-grade magnesite tailings aggregate with a particle size of 0.25-20 mm: 55wt%, of which 0.25mm≤particle size<5.0mm accounts for 45wt%, and 5.0mm≤particle size<20mm accounts for 55wt%;

[0065] Admixture: 30wt%;

[0066] Admixture: 5wt%;

[0067] Binder: 10wt%;

[0068] The admixture is low-grade magnesite tailings, 3wt% magnesium chloride powder is added, and the fine powder of calcined and ground clinker particles is obtained, wherein particles with a particle size of 0.088mm≤≤0.25mm account for 20wt%, and particles with a particle size of ≤0.088mm account for 80wt%;

[0069] The admixture comprises the following raw materials in weight percentage: 2.2wt% SiO2 ultrafine powder, 2.2wt% Al2O3 powder, 0.45wt% hydroxypropyl methylcellulose (HPMC), 0.1% sodium tripolyphosphate, and 0.05% sodium hexametaphosphate;

[0070] The binder is a mixture of water glass, ethyl silicate and polyaluminium chloride, wherein the weight percentage of water glass, ethyl silicate and polyaluminium chloride is 5.5:0.3:0.03.

[0071] Furthermore, the SiO2 content in the SiO2 ultrafine powder is greater than 98wt% and the particle size is less than 1μm;

[0072] Furthermore, the particle size of the Al2O3 powder is less than 0.088 mm.

[0073] Furthermore, a method for preparing a magnesium castable using low-grade magnesite tailings as aggregate comprises the following steps:

[0074] Step 1: crush and screen the selected low-grade magnesite tailings, and select the particles with a particle size of 0.25 to 20 mm as the low-grade magnesite tailings coarse material, i.e., aggregate, wherein the particles with a particle size of 0.25 mm ≤ < 5.0 mm and the particles with a particle size of 5.0 mm ≤ < 20 mm are placed in a classified manner for the convenience of weighing and batching later;

[0075] Step 2: Add 3 wt% of magnesium chloride powder to the remaining materials screened in step 1, i.e., low-grade magnesite tailings with a particle size of less than 0.25 mm and a particle size of ≥20 mm, calcine at 930° C. for 2.5 h, and then crush, grind and screen to obtain fine powder with a particle size of less than 0.088 mm and granular material with a particle size of 0.088 to 0.25 mm, i.e., admixture;

[0076] Step 3, weighing 30wt% of the admixture and 5wt% of the admixture according to weight percentage, putting them into a vibration mill and grinding them for 10 minutes to obtain a mixture;

[0077] Step 4: Weigh 55wt% of the aggregate prepared in step 1 by weight percentage, of which 45wt% are particles with a diameter of 0.25mm≤<5.0mm, 55wt% are particles with a diameter of 5.0mm≤<20mm, and 10wt% are binders. Add them together with the mixture prepared in step 3 into a mixer and stir for 5 minutes to obtain a castable.

[0078] [Example 3]

[0079] A magnesium castable with low-grade magnesite tailings as aggregate, which is made of low-grade magnesite tailings aggregate with a particle size of 0.25 to 20 mm, admixtures, additives and binders, and the proportions of each component by weight are as follows:

[0080] Low-grade magnesite tailings aggregate with a particle size of 0.25-20 mm: 65wt%, of which 0.25mm≤particle size<5.0mm accounts for 50wt%, 5.0mm≤particle size<20mm accounts for 50wt%;

[0081] Admixture: 20wt%;

[0082] Admixture: 8wt%;

[0083] Binder: 7wt%;

[0084] The admixture is low-grade magnesite tailings, 1wt% magnesium chloride powder is added, and the fine powder of calcined and ground clinker particles is obtained, wherein 0.088mm≤particle size≤0.25mm accounts for 30wt%, and particle size≤0.088mm accounts for 70wt%;

[0085] The admixture comprises the following raw materials in weight percentage: 3.5wt% SiO2 ultrafine powder, 3.5wt% Al2O3 powder, 0.75wt% hydroxypropyl methylcellulose (HPMC), 0.15% sodium tripolyphosphate, and 0.1% sodium hexametaphosphate;

[0086] The binder is a mixture of water glass, ethyl silicate and polyaluminium chloride, wherein the weight percentages of water glass, ethyl silicate and polyaluminium chloride are 4.5:0.3:0.04.

[0087] Furthermore, the SiO2 content in the SiO2 ultrafine powder is greater than 98wt% and the particle size is less than 1μm;

[0088] Furthermore, the particle size of the Al2O3 powder is less than 0.088 mm.

[0089] Furthermore, a method for preparing a magnesium castable using low-grade magnesite tailings as aggregate comprises the following steps:

[0090] Step 1: crush and screen the selected low-grade magnesite tailings, and select the particles with a particle size of 0.25 to 20 mm as the low-grade magnesite tailings coarse material, i.e., aggregate, wherein the particles with a particle size of 0.25 mm ≤ < 5.0 mm and the particles with a particle size of 5.0 mm ≤ < 20 mm are placed in a classified manner for the convenience of weighing and batching later;

[0091] Step 2, adding 1wt% of magnesium chloride powder to the remaining materials screened in step 1, i.e., low-grade magnesite tailings with a particle size of less than 0.25mm and a particle size of ≥20mm, calcining at 980°C for 3h, and then crushing, grinding and screening to obtain fine powder with a particle size of less than 0.088mm and granular material with a particle size of 0.088-0.25mm, i.e., admixture;

[0092] Step 3, weighing 20wt% of the admixture and 8wt% of the admixture according to weight percentage, putting them into a vibration mill and grinding them for 10 minutes to obtain a mixture;

[0093] Step 4: Weigh 65wt% of the aggregate prepared in step 1 by weight percentage, of which 50wt% are particles with a diameter of 0.25mm≤<5.0mm, 50wt% are particles with a diameter of 5.0mm≤<20mm, and 7wt% are binders. Add them together with the mixture prepared in step 3 into a mixer and stir for 5 minutes to obtain a castable.

[0094] According to conventional testing methods, various performance indicators such as volume density, compressive strength, flexural strength, etc. of the above-mentioned embodiments are tested and shown in Table 1.

[0095] Table 1

[0096]

[0097] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A magnesium castable using low-grade magnesite tailings as aggregate, characterized in that: The castable is made of low-grade magnesite tailings aggregate with a particle size of 0.25 to 20 mm, admixtures, additives and binders, and the proportions of each component by weight are as follows: Low-grade magnesite tailings aggregate with a particle size of 0.25-20mm: 55-65wt%, of which 0.25mm≤particle size<5.0mm accounts for 45-50wt%, 5.0mm≤particle size<20mm accounts for 50-55wt%; Admixture: 20-30wt%; Admixture: 5-8wt%; Binder: 7-10wt%; The admixture is low-grade magnesite tailings, 1-3wt% magnesium chloride powder is added, and the fine powder of calcined and ground clinker particles is obtained, wherein particles with a particle size of 0.088 mm or less and a particle size of 0.25 mm or less account for 20-30wt%, and particles with a particle size of 0.088 mm or less account for 70-80wt%. The admixture comprises the following raw materials in weight percentage: 2-4wt% SiO2 ultrafine powder, 2-4wt% Al2O3 powder, 0.1-0.8wt% hydroxypropyl methylcellulose (HPMC), 0.1-0.15% sodium tripolyphosphate, and 0.05-0.1% sodium hexametaphosphate; The binder is a mixture of water glass, ethyl silicate and polyaluminium chloride, wherein the weight percentages of water glass, ethyl silicate and polyaluminium chloride are 4-6:0.3-0.7:0.03-0.

07.

2. The method for preparing a magnesia castable using low-grade magnesite tailings as aggregate according to claim 1, characterized in that: The following steps are involved: Step 1: crush and screen the selected low-grade magnesite tailings, and select the particles with a particle size of 0.25 to 20 mm as the low-grade magnesite tailings coarse material, i.e., aggregate, wherein the particles with a particle size of 0.25 mm ≤ < 5.0 mm and the particles with a particle size of 5.0 mm ≤ < 20 mm are classified and placed; Step 2, adding 1-3wt% magnesium chloride powder to the remaining materials screened in step 1, calcining at 900-1000°C for 1-3h, and then crushing, grinding and screening to obtain fine powder with a particle size of less than 0.088mm and granular material with a particle size of 0.088-0.25mm, i.e., admixture; Step 3, weighing 20-30 wt% of admixture and 5-8 wt% of admixture according to weight percentage, putting them into a vibration mill and grinding them for 10 minutes to obtain a mixture; Step 4: weigh 55-65wt% of the aggregate prepared in step 1 and 7-10wt% of the binder by weight percentage, add them together with the mixture prepared in step 3 into a mixer, and stir for 3-5 minutes to obtain a castable.

3. A magnesia castable with low-grade magnesite tailings as aggregate according to claim 1, characterized in that: It includes the following components in parts by weight: Low-grade magnesite tailings aggregate with a particle size of 0.25-20 mm: 60wt%, of which 0.25mm≤particle size<5.0mm accounts for 47.5wt%, and 5.0mm≤particle size<20mm accounts for 52.5wt%; Admixture: 25wt%; Admixture: 6.5wt%; Binder: 8.5wt%.

4. The magnesia castable with low-grade magnesite tailings as aggregate according to claim 1, characterized in that: The admixture is low-grade magnesite tailings, calcined and ground clinker particle fine powder with 2wt% magnesium chloride powder added thereto, wherein particles with a size of 0.088mm≤≤0.25mm account for 25wt%, and particles with a size of ≤0.088mm account for 75wt%.

5. The magnesia castable with low-grade magnesite tailings as aggregate according to claim 1, characterized in that: The additive comprises the following raw materials in weight percentage: 2.9wt% SiO2 ultrafine powder, 2.9wt% Al2O3 powder, 0.5wt% hydroxypropyl methylcellulose (HPMC), 0.125% sodium tripolyphosphate, and 0.075% sodium hexametaphosphate.

6. The magnesia castable with low-grade magnesite tailings as aggregate according to claim 1, characterized in that: The binder is a mixture of water glass, ethyl silicate and polyaluminium chloride, wherein the weight percentage of water glass, ethyl silicate and polyaluminium chloride is 5:0.5:0.05.